FIELD STUDIES OF THE DYNAMICS OF THE CHANNEL PROCESS ON THE AMUDARYA RIVER BELOW THE TUYAMUYUN - Rakhmatov Norqabul XXX; Japakov Norboy Buriboevich; Akhatov son of Samandar Anvar (European Science Publishing, 2024)
In this article, the reasons for carrying out riverbed correction works in rivers with a changing course, the analysis of the results of scientific research carried out by foreign and our republican researchers on the issues of ensuring the stability of the corrected riverbed section are covered.
Keywords: River, channel, coast, protection, hydrotechnical structure, water speed, straightening structures, water intake without dam, spur.